2018
DOI: 10.1002/term.2633
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing human decellularized crystalline lens capsules as a scaffold for corneal endothelial tissue engineering

Abstract: The idea of transplanting a sheet of laboratory‐grown corneal endothelium dates back to 1978; however, the ideal scaffold is still lacking. We hypothesized that human crystalline lens capsules (LCs) could qualify as a scaffold and aimed to characterize the properties of this material for endothelial tissue engineering. LCs were isolated from donor eyes, stored at −80 °C, and decellularized with water and trypsin‐EDTA. The decellularization was investigated by nuclear staining and counting and the capsule thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 38 publications
1
39
0
2
Order By: Relevance
“…However, after transplantation into rabbits, the corneas gradually regained transparency and the angiogenesis that developed immediately after transplantation started to regress after the first 2 weeks . Van den Bogerd et al have successfully used the freeze‐thaw method on anterior capsule of the lens to make a useful scaffold for corneal endothelial cells (CECs).…”
Section: Decellularization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after transplantation into rabbits, the corneas gradually regained transparency and the angiogenesis that developed immediately after transplantation started to regress after the first 2 weeks . Van den Bogerd et al have successfully used the freeze‐thaw method on anterior capsule of the lens to make a useful scaffold for corneal endothelial cells (CECs).…”
Section: Decellularization Methodsmentioning
confidence: 99%
“…A comparative study found that the acellular human lens capsule is a better scaffold to create ES when compared with human Descemet's membranes and human amniotic membranes. 50 In animal studies, freeze-thaw, N 2 gas, HHP, and SDS-treated DPCXs displayed repopulation of recipient keratocytes in graft stroma after lamellar keratoplasty. 10,22,48,51 However, the recellularization activity of PLA and glycerol combined with chemical crosslinking seems to be a preferred alternative.…”
Section: Recellul Ariz Ationmentioning
confidence: 97%
See 1 more Smart Citation
“…Endo: corneal endothelium medium; Exofree: BM MSC medium with exosome depleted FBS; WT FBS: BM MSC medium with wild-type FBS. 4 Stem Cells International identified growth factors, there was neither a simulation of growth, even more, there was an increase in PDT, i.e., a slower cell growth, for cell supplemented with a 10 ng/mL combination of EGF-IGFBP2-IGFBP6 (Figure 7(g)).…”
Section: Growth Factor Titrationmentioning
confidence: 99%
“…One possible strategy to overcome these issues is to tissue engineer an endothelial layer in the lab. This product would be composed of ex vivo grown HCEnCs on a suitable cell scaffold for transplantation [1,4,5]. Although the scaffold approach is the most commonly explored, cell suspension therapies have also been trialed in 11 patients [6,7].…”
Section: Introductionmentioning
confidence: 99%